Семантика ікони в знаковій системі авангарду - Столярчук, Н. М.; Stolyarchuk, N. M. (Східноєвропейський національний університет імені Лесі Українки, 2013)
У статті проаналізовано комплекс семантичних прийомів православного іконопису, який став основою для формування знакової системи авангардного мистецтва в його прагненні репрезентувати сакральне; дове-дено, що спільним змістом образів православної ікони й авангардного мистецтва є концепти «ідеї», «духу», «абсолюту» як головні об’єкти зображення, що створюють символічний простір і породжують трансцендентне. This article analyzes the complex semantic techniques of Orthodox iconography, which became the basis for the formation of the sign system of avant-garde art in its quest for representation of the sacred; It is proved that the General content of the image for Orthodox icons and their avant-garde art are the concepts of «idea», «spirit», «absolute» as the main objects in the image, creating a symbolic space and giving rise to transcendent. The influence of the Orthodox icons on the aesthetics of avant-garde artists on two levels: theoretical (philosophical and theological understanding icons and spiritually-aesthetic avant-garde spirit); practical (artistic language icons and some of the principles of the art of avant-garde work). Key words: icon, sign, symbol, image, sacred, transcendent, deformation, inverse perspective, vanguard.
The Semantics of the Icons in the Vanguard of the Sign System
Keywords: ікона; icon; знак; sign; символ; symbol; образ; image; сакральне; sacred; трансцендентне; transcendent; vanguard; авангард